Super-Charged Natural Killer Cells: A Promising Immunotherapeutic Strategy for Oral Cancer - Kawaljit Kaur; Anahid Jewett (Immuno)
NK cells have traditionally been classified as effectors of innate immunity, even though they also exhibit some features of adaptive immunity such as memory. NK cells contribute to the lysis and growth inhibition of cancer, mediating direct cytotoxicity and antibody-dependent cellular cytotoxicity (ADCC) and regulating the functions of other immune cells, respectively. NK cells regulate the function of other immune cells via the release of inflammatory cytokines and chemokines. Currently, NK cell therapeutics in oral cancer have been less efficient due to several limitations, as follows: (a) lower percentages of NK cells in peripheral blood immune cells; (b) limited survival and decreased function of NK cells, especially in the tumor microenvironment; and (c) a lack of tools or methodologies to expand and activate NK cells to the levels that are required for the effective targeting of oral cancer. To overcome these limitations, we established and demonstrated a novel technology for activating and expanding highly functional NK cells coined as supercharged NK (sNK) cells. This review summarizes the characteristics of sNK cells and highlights their superior anti-cancer activity when compared to primary activated NK cells.